Cover Feature: Phosphinine‐Based Ligands in Gold‐Catalyzed Reactions (Chem. Eur. J. 37/2019). Issue 37 (21st May 2019) - Rigo, Massimo; Habraken, Evi R. M.; Bhattacharyya, Koyel; Weber, Manuela; Ehlers, Andreas W.; Mézailles, Nicolas; Slootweg, J. Chris; Müller, Christian
Abstract : Once upon a time there was a phosphinine… The heteroaromatic phosphinines are versatile starting materials for the design of new phosphorus‐based ligands. The present manuscript reports on the synthesis of a series of substituted phosphinines and the related 1‐phosphabarrelenes and 5‐phosphasemibullvalene derivatives. The steric and electronic properties of these ligands were evaluated both by means of theoretical and experimental methods. The corresponding gold(I) complexes were subsequently applied in homogeneous Au‐catalyzed cycloisomerization reactions, showing very good activities and selectivities. More information can be found in the Full Paper by C. Müller, et al. on page 8769 .